Energy Balance Regulating Neuropeptides Are Expressed through Pregnancy and Regulated by Interleukin-6 Deficiency in Mouse Placenta - Patricia Pazos; Luis Lima; Carlos Diéguez; María C. García (International Journal of Endocrinology)
The placenta produces a number of signaling molecules including metabolic and reproductive hormones as well as several inflammatory mediators. Among them, Interleukin-6 (IL-6), a well-known immune and metabolic regulator, acts peripherally modulating metabolic function and centrally increasing energy expenditure and reducing body fat. IL-6 interacts with key hypothalamic neuropeptidergic systems controlling energy homeostasis such as those producing the orexigenic/anabolic: neuropeptide Y (NPY) and agouti-related peptide (AgRP) and anorectic/catabolic neuropeptides: proopiomelanocortin (POMC) and cocaine and amphetamine regulated transcript (CART). Human and rat placenta have been identified as source of these neuropeptides, but their expression and regulation in murine placental tissues remain unknown. Therefore, placental mRNA levels of IL-6, NPY, AgRP, POMC, and CART at different pregnancy stages (gestational days 13, 15, and 18) were analyzed by real time PCR, as were the effect of IL-6 deficiency (IL-6 knockout mice) on their placental expression. Our results showed that placenta-derived neuropeptides were regulated by gestational age and IL-6 throughout the second half of mouse pregnancy. These data suggest that IL-6 may participate in the fine tune control of energy balance during pregnancy by extending its action as a metabolic signal to the main organ at the fetomaternal interface: the placenta.